Synopsis, Economics of land degradation and improvement: A global assessment for sustainable development - Nkonya, Ephraim M.; Mirzabaev, Alisher; von Braun, Joachim (International Food Policy Research Institute, 2015)
The costs of doing nothing about land degradation are several times higher than the costs of taking action to reverse it. Despite the crucial role land plays in human welfare and development, investments in sustainable land management are low, especially in developing countries. These findings come from the book, Economics of Land Degradation and Improvement—A Global Assessment for Sustainable Development, which examines the costs of land degradation and what needs to be done to reverse it. The book reveals the cost of land degradation in case studies for 12 countries, analyzes the drivers, and identifies strategies for sustainable land management. It focuses on two kinds of land degradation: long-term loss of value of land ecosystem services due to land use and cover change (LUCC) and the use of land-degrading management practices on cropland and grazing lands that do not undergo LUCC. Six major biomes that accounted for about 86 percent of global land area in 2001 are covered, including forest, shrub lands, grasslands, cropland, barren land, and woodlands. Thirty-three percent of grasslands, 25 percent of croplands, and 23 percent of forests experienced degradation over the last three decades.